Demand-side shared energy storage pricing strategy based on stackelberg-Nash game - Jindong Cui; Zengchen Zhu; Guoli Qu; Yuqing Wang; Ruotong Li (International Journal of Electrical Power & Energy Systems)
With the large-scale access of user-side energy storage devices, shared energy storage has emerged as a key mode of energy storage in distribution networks. This mode requires efficient management of energy storage devices that balances the interests of different entities such as power supply enterprises, shared energy storage operators, and prosumers. In this mode, the formulation of charging and discharging prices is crucial. This paper proposed a dual-layer pricing model for shared energy storage systems based on mixed-game theory and its solution method. First, this study developed an upper-level stackelberg game model between the power supply enterprise and the cooperative alliance. The power supply enterprise, acting as the leader, sought to minimize operational costs while negotiating transaction electricity prices with the cooperative alliance. Second, a cooperative game model was developed within the lower-level alliance. As followers, the cooperative alliance seeks to maximize the alliance’s overall benefits. Based on the upper-level transaction electricity price and Nash bargaining theory, the internal transaction electricity price within the alliance was determined through negotiation. Subsequently, charging and discharging strategies were formulated along with a profit distribution mechanism. Finally, case studies simulations were used to validate the feasibility and effectiveness of the proposed model.